Cultural identity, language ability, and their relationship among Chinese preschoolers in Singapore - Teng, Venice Wen Si (2019)
Mandarin proficiency in Singapore has been declining over the years (Chia, 2013; C. L. Lee, 2012; Ng, 2014) and it is important to investigate factors related to language ability to inform future policies aiming to increase Mandarin proficiency. Existing research on the relationship between cultural identity and language ability has been inconclusive and past studies were not conducted in a multicultural and bilingual context like Singapore. In this study, the relationship between Chinese and Western cultural identity and the corresponding language vocabulary performance of preschoolers in Singapore were examined. The Chinese and Western cultural identity, as well as Mandarin and English receptive vocabulary of Chinese preschoolers aged five to six years (N = 41), were measured. Results demonstrated that preschoolers had a dominant Western cultural identity and were dominant in the English language. It was found that preschoolers who identified more strongly with the Western culture had higher English vocabulary performance, but this was not the case for Chinese cultural identity and Mandarin vocabulary performance. Preschoolers’ self-reported Western cultural identity was discovered to be a predictor of English vocabulary performance, but parental reports of preschoolers’ Western cultural identity was not a predictor. Theoretical and practical implications of the findings were discussed.